Pengaruh Ketepatan Waktu Pengiriman dan Fasilitas Tracking System Terhadap Kepuasan Pelanggan J&T Express - Mercy Spesa Devina De Fretes; Dwi Seftia Vandiani (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.This study aims to analyze the effect of delivery timeliness and tracking system facilities on customersatisfaction with J&T Express. The sample in this study consists of J&T Express customers in MutiaraGading City. This study used a quantitative approach, with a sample size of 100 people selected using nonprobability sampling techniques. Data processing was conducted using IBM SPSS version 30.0.0.0. Theresults of this study indicated that delivery timeliness has a positive and significant effect on customersatisfaction, with a value of 4.910. The tracking system facility has a positive and significant effect oncustomer satisfaction, with a value of 5.015. The simultaneous test results showed that delivery timelinessand tracking system facilities together have a positive and significant effect on customer satisfaction witha significance value <0.001 less than 0.05. The magnitude of the effect of delivery timeliness is 55.4%, trackingsystem facilities 55.8%, and simultaneously 64.6%.Keywords: Delivery Timeliness, Tracking System Facilities, Customer Satisfaction